A systematic review of knowledge, attitudes and beliefs about malaria among the South Asian population. Issue 1 (1st January 2016) - Regmi, Krishna; Kunwar, Anju; Ortega, Leonard
Abstract : Background: Malaria is one of the deadliest mosquito-borne diseases in the world. More than 80% of the total populations are at risk of malaria in the 22 countries in Asia and the Pacific. South Asia alone is home to an estimated 1.4 billion people at risk of contracting malaria. Despite the remarkable progress in reducing the burden of malaria, evidence of the disease based on knowledge of the social and cultural contexts from a South Asian perspective is limited. Our objective was to understand the knowledge, attitudes and beliefs about malaria in South Asian communities. Methodology: We conducted a systematic literature review, searching six databases, between 1990 and 2015, focusing on knowledge, attitudes and beliefs about malaria in South Asia. Databases were searched using both 'free terms' and 'index terms' funnelled using Boolean operators and truncations. Inclusion and exclusion criteria were set, and included papers were scrutinised, employing a critical appraisal tool to find the best available evidences to support the study purpose. Results and discussion: Evidence from 32 articles (26 quantitative, four qualitative and two mixed methods). General knowledge and awareness of the disease, its transmission, and control and preventative measures were generally found to be lacking amongst both the general public and healthcare professionals. In addition, the study shows that poor socio-economic factors – including limited access to services due to poor/limited availability – and issues of affordability are considered as major risk factors. Conclusion: This review suggests the importance of increasing health awareness, mobilising the local or community healthcare professionals, for prevention as well as early detection and effective treatment of malaria among people who are at risk. Malaria is also a disease associated with poverty and socio-cultural factors; therefore, strong political will, wider partnerships between health and non-health sectors, and strengthening health systems' technical and managerial capabilities at all level of primary healthcare systems, is inevitable.